Factors associated with population coverage of targeted malaria elimination (TME) in southern Savannakhet Province, Lao PDR - Bipin Adhikari (Malaria Journal, 2017)
Abstract Background Targeted malaria elimination (TME) in Lao PDR (Laos) included three rounds of mass drug administrations (MDA) against malaria followed by quarterly blood surveys in two villages in Nong District at Savannakhet Province. The success of MDA largely depends upon the efficacy of the anti-malarial drug regimen, local malaria epidemiology and the population coverage. In order to explore the reasons for participation in TME, a quantitative survey was conducted after the completion of the three rounds of MDA. Methods The survey was conducted in two villages with a total of 158 households in July and August 2016. Among the 973 villagers eligible for participation in the MDA, 158 (16.2%) adults (> 18 years) were selected, one each from every household for the interviews using a quantitative questionnaire. Results 150/158 (94.9%) respondents participated at least in one activity (taking medicine or testing their blood) of TME. 141/150 (94.0%) respondents took part in the MDA and tested their blood in all three rounds. 17/158 (10.7%) were partial or non-participants in three rounds of MDA. Characteristics of respondents which were independently associated with completion of three rounds of MDA included: attending TME meetings [AOR = 12.0 (95% CI 1.1–20.5) (p = 0.03)], knowing that malaria can be diagnosed through blood tests [AOR = 5.6 (95% CI 1.0–32.3) (p = 0.05)], all members from household participated [AOR = 4.2 (95% CI 1.3–14.0) (p = 0.02)], liking all aspects of TME [AOR = 17.2 (95% CI 1.6–177.9) (p = 0.02)] and the perception that TME was important [AOR = 14.9 (95% CI 1.3–171.2) (p = 0.03)]. Conclusion Complete participation in TME was significantly associated with participation in community engagement activities, knowledge that the blood tests were for malaria diagnosis, family members’ participation at TME and perceptions that TME was worthwhile. A responsive approach to community engagement that includes formative research and the involvement of community members may increase the uptake of the intervention.